Organ-on-a-chip with integrated semitransparent organic electrodes for barrier function monitoring. Issue 7 (22nd February 2023) - Marrero, Denise; Guimera, Anton; Maes, Laure; Villa, Rosa; Alvarez, Mar; Illa, Xavi
Abstract : We propose an OoC with semitransparent PEDOT:PSS electrodes for barrier function monitoring where we evaluate barrier tightness, integrity, and the intercellular cleft of intestinal cells. Abstract : Organs-on-a-chip (OoC) are cell culture platforms that replicate key functional units of tissues in vitro . Barrier integrity and permeability evaluation are of utmost importance when studying barrier-forming tissues. Impedance spectroscopy is a powerful tool and is widely used to monitor barrier permeability and integrity in real-time. However, data comparison across devices is misleading due to the generation of a non-homogenous field across the tissue barrier, making impedance data normalization very challenging. In this work, we address this issue by integrating PEDOT:PSS electrodes for barrier function monitoring with impedance spectroscopy. The semitransparent PEDOT:PSS electrodes cover the entire cell culture membrane providing a homogenous electric field across the entire membrane making the cell culture area equally accountable to the measured impedance. To the best of our knowledge, PEDOT:PSS has never been used solely to monitor the impedance of cellular barriers while enabling optical inspection in the OoC. The performance of the device is demonstrated by lining the device with intestinal cells where we monitored barrier formation under flow conditions, as well as barrier disruption and recovery under exposure to a permeability enhancer. The barrier tightness and integrity, and the intercellular cleft have been evaluated by analyzing the full impedance spectrum. Furthermore, the device is autoclavable paving the way toward more sustainable OoC options.